INBONE Total Ankle System: Clinical and Radiographic Outcomes. Issue 4 (November 2022) - Padley, Michelle A.; Albert, Andrew J.; Anderson, John G.; Bohay, Donald R.; Maskill, John D.; McKearney, Daniel A.; Phillips, Alexander; Potter, Ramsey S.; Kothari, Parin D.
Category: Ankle Arthritis Introduction/Purpose: Ankle arthroplasties have undergone several generations of development since their initial introduction. Newer technologies in design have offered prosthetics which were more mobile and closer in articulation to human ankle joints. This includes increased motion of the coronal and sagittal planes, as well as less wear-and-tear of the prosthesis. Currently, second generation ankle arthroplasties have only shown promising results intermediately, and there has been very little research looking into the long term results of these devices. The INBONE total ankle system is a relatively new addition to the market that specifically has not been well researched. This project is aimed to outline their morbidly and mortality, as well as compare the long term results to other commonly used implants with data available. Methods: The study will be a retrospective, single-site cohort of past patients who have undergone INBONE total arthroplasty by Drs. Anderson, Bohay and Maskill at Orthopaedic Associates of Michigan (OAM). Pre-op indications will be evaluated, as well as lengthy post-op periods including 2 week, 6 week, 8 week, 1 year, and 2+ years follow up scores. Charts will be reviewed for inclusion and exclusion criteria. This includes demographic information, operative information, complications, reoperations, radiographic outcomes, and post-operative satisfaction scores. These scores include functional characteristics of ankle arthritis patients including pain level, walking distances, gait stability, varus/valgus stress, dorsi/plantarflexion ankle motion arc, hindfoot stability, and ankle alignment (AOFAS Score Criteria). Results: Study still in progress, results pending. Conclusion: Study still in progress, results pending.